2019
DOI: 10.3389/fphar.2019.00025
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Adonis as an Important Cardiac Folk Medicine: A Review of the Ethnobotany, Phytochemistry and Pharmacology

Abstract: The genus Adonis L. (Ranunculaceae), native to Europe and Asia, comprises 32 annual or perennial herbaceous species. Due to their cardiac-enhancing effects, Adonis spp. have long been used in European and Chinese folk medicine. These plants have been widely investigated since the late 19th century, when the cardiovascular activity of Adonis vernalis L. was noted in Europe. The present paper provides a review of the phytochemistry, biological activities and toxicology in order to highlight the future prospects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 71 publications
(106 reference statements)
1
22
0
Order By: Relevance
“…Triterpenoid toosendanin (TSN) is a main bioactive component of fruits and bark of traditional anthelmintic and insecticidal plants Melia azedarach and Melia toosendan . Toosendanin has antibotulinum (inhibits the botulinum neurotoxin interaction with the SNARE protein), anti-influenza (alters nuclear localization of viral polymerase PA protein), anticancer, anti-inflammatory, and analgesic (selective presynaptic blocker) efficacy [ 310 , 311 ]. Possible actions of TSN as an antitumor drug against a variety of cancer types involve inhibition of STAT3, an emerging target for cancer therapy, induction of estrogen receptor β (ERβ) and p53 proteins, and activation of the mitochondrial apoptotic pathway [ 312 , 313 , 314 ].…”
Section: Plant-derived Bioactive Natural Products From Fungal Endomentioning
confidence: 99%
“…Triterpenoid toosendanin (TSN) is a main bioactive component of fruits and bark of traditional anthelmintic and insecticidal plants Melia azedarach and Melia toosendan . Toosendanin has antibotulinum (inhibits the botulinum neurotoxin interaction with the SNARE protein), anti-influenza (alters nuclear localization of viral polymerase PA protein), anticancer, anti-inflammatory, and analgesic (selective presynaptic blocker) efficacy [ 310 , 311 ]. Possible actions of TSN as an antitumor drug against a variety of cancer types involve inhibition of STAT3, an emerging target for cancer therapy, induction of estrogen receptor β (ERβ) and p53 proteins, and activation of the mitochondrial apoptotic pathway [ 312 , 313 , 314 ].…”
Section: Plant-derived Bioactive Natural Products From Fungal Endomentioning
confidence: 99%
“…When analyzing a homogeneous group of substances such as a phytocomplex, the differences between the two methods must be three to five times a day (Sokolov, 2000). The mechanism of action is similar to digitoxin with inhibition of the membrane protein Na + /K + -ATPase in muscle tissue of the heart, resulting in Ca 2+ overload, diastolic dysfunction, arrhythmias, heart failure and death (Shang et al, 2019).…”
Section: Qualitative and Quantitative Analysis Of Plant Extractsmentioning
confidence: 99%
“…Adonis vernalis L. is an attractive yellow flower of the Ranunculaceae family, flowering in the spring (Figure 2) (Lattè, 2018). Extracts of the plant first appeared in cardiac‐stimulating medicine, in 1879, but were later used mixed with sodium (or potassium) bromide or codeine to treat light forms of epilepsy and heart disease (Shang et al, 2019). The herbal drug derived from the plant’s aerial parts is a cardiac stimulant.…”
Section: Paradox Of the Assessment Of Adonis Vernalismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the members of the Adonis genus are not appropriate for cultivation due to the presence of toxic alkaloids. The extracts and active components of A. vernalis, A. volgensis, A. courule and A. amurensis exhibit widespread pharmacological properties (antiinflammatory, cardiovascular, antiviral, antiangiogenic and diuretic effects, and antioxidant, antibacterial and acaricidal activities) [21]. Members of this genus have been reported to cause toxicity due to their adonitoxin and other cardiac glycoside (cardenolides) content [14,28].…”
Section: Introductionmentioning
confidence: 99%